Beyond the “Raked Gardens”: Female Identity in American Suburban Poetry - Flajšar, Jiří (Hungarian Journal of English and American Studies, 2021)
The article analyzes an overlooked aspect of American suburban poetry—the writing of American women poets who deal with the problem of how to represent female identity. Drawing on the existing criticism of women’s poetry, a comprehensive survey of the suburban poems by American women poets, from the 1940s to the 2000s, is provided. The article documents the various approaches that these poets adopt in order to explore identity while resisting the gender stereotypization in American suburbia. These approaches include either embracing the suburban ideal of domestic conformity or attempting to present women suburbanites who reject the socially prescribed roles forced upon them and develop new identities of their own. (JF)